Rola związków zawodowych w stanowieniu wewnątrzzakładowych regulaminów pracy - Gajda, Mateusz; Kraśniewski, Marcin (Kwartalnik Prawa Publicznego, 2016)
The purpose of this article is to present legal basis of participation of the trade unions in the process of establishing workplace bylaws, including workplace regulations, remuneration regulations and social benefits fund regulations. The authors of the article describe the most important reasons which justify why the trade unions are entitled to take part in the process of introducing bylaws. Moreover, authors examine the recent changes of the Labour Code which grant trade unions new entitlements. Taking into account, new wording of the statutory law, it seems that the main role of the trade unions is to protect workers interests by refraining the employer from introducing bylaws which are not compliant with the provisions of the Polish law. Importantly, such activity may both increase the level of employee’s protection as well as secure employer’s interests.